PELAYANAN GEREJA TERHADAP KAUM LANSIA DI MASA PANDEMI COVID-19 DITINJAU DARI IBRANI 10:25 - Sumiran Winarto (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2021)
This study aimed to explain the extent of the physical condition of the elderly, the ability to understand technology, and the understanding of online worship towards online worship during the Covid-19 pandemic. The research method used is descriptive quantitative. The researcher conducted questionnaires and interviews with 50 elderly in the Seventh Day Adventist Magetan and Poncol churches in East Java. The results showed that the elderly had difficulty participating in online worship because their eyesight and hearing decreased. They did not have a smartphone and could not run them for worship. They are more likely to expect services at home and to be served through pastor dan elders visitation.